Talents, Preferences and Inequality of Well-Being - Udo Ebert; Patrick Moyes (University of Oldenburg, Department of Economics, 2010)
The distribution of gross income net of taxes and transfers - or equivalenty consumption - is generally considered a reasonable approximation of the distribution of well-being in the society. One typically observes differing trends in the distribution of gross incomes across countries or within the same country over time. Where do these inequalities originate from? Considering a simple model with no taxation and where individuals belonging to the same society have identical preferences but different productivities, we investigate the impact on the distribution of gross income of changes in the way productivities are distributed. We also look for those changes in the common preference ordering that result in more equally distributed incomes when the allocation of productivities is fixed. Finally, we want to know how preferences have to be adjusted for less dispersed talents to always imply more evenly distributed incomes.
Keywords: D31; D61; 330; Well-Being; Inequality; Talents; Preferences; Lorenz Dominance